Sustainable Tourism in Sundarbans UNESCO Site: Challenges and Proposals for Conservation and Community Benefits - Faruk Hossain; Md. Asikur Rahman; Sazu Sardar; Md Sohanur Rahman Shohan (Journal of Sustainable Tourism and Entrepreneurship, 2026)
Purpose: This study analyzes the Strengths, Weaknesses, Opportunities, and Threats (SWOT) of the Sundarbans to support sustainable tourism development. It identifies the key barriers and prospects influencing sustainability in this ecologically sensitive region. Research Methodology: This qualitative study in Shyamnagar Upazila, Satkhira, Bangladesh, used 25 in-depth interviews with farmers, fishermen, honey collectors, and boat operators to collect data. Data from official reports and documents were collected. The thematic analysis and SWOT framework identified key challenges and opportunities for sustainable tourism development in the region. Results: Most respondents were middle-aged male fishers with low income and education, indicating high vulnerability. Strengths include rich biodiversity and eco-tourism potential, while weaknesses involve poverty, lack of awareness, and poor infrastructure. Opportunities lie in eco-tourism and community-based tourism, while threats include climate change and illegal resource use. Conclusions: This study concludes that sustainable tourism in Shyamnagar depends on integrated governance, community participation, and conservation-oriented planning. These findings contribute to a better understanding of conservation–livelihood linkages and provide practical insights for policymakers and other stakeholders. Limitations: This study was limited by its small sample size and qualitative scope. Future research should use larger samples and mixed-methods. Policies should focus on awareness, infrastructure, and community management. Contributions: This study provides empirical evidence of conservation-tourism linkages in Shyamnagar Upazila, Sundarbans, emphasizing community participation and livelihoods. This study offers practical insights for policymakers, conservationists, and development actors to promote sustainable tourism and heritage management.